PENGARUH FREE CASH FLOW, INVESTMENT OPPORTUNITY SET, DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN FOOD AND BEVERAGE - Fitri, Nur Laela; Pangaribuan, David; Yuniati, Triana (SENTRI: Jurnal Riset Ilmiah, 2024)
The purpose of this study is to test and analyze the effect of free cash flow, investment opportunity set, and capital structure on dividend policy. This research method uses quantitative research methods, with the type and source of data, namely secondary data obtained from the company’s annual financial reports. The population is all food and beverage companies which are listed in Indonesia Stock Exchange (IDX) in 2018-2022 periods. The sample collection technique has been done by using purposive sampling so that 105 samples of food and beverage companies which meet the criteria have been selected as the research samples. The analytical method used is descriptive statistical test, classical assumption test, regression test with multiple linear regression and hypothesis testing. The result shows that free cash flow gives positive influence to the dividend policy, investment opportunity set gives negative influence to the dividend policy, and capital structure gives positive influence to the dividend policy. Free cash flow, investment opportunity set, and capital structure simultaneously have significant effect toward dividend policy.